Effect evaluation of case-based learning with situated cognition theory on competence training for student nurses in pediatric surgery. Issue 2 (February 2023) - Wang, Miyan; Chen, Xiaohong; Yang, Yuwei; Wang, Haiyan; Yan, Yan; Huang, Xiaoying; Bi, Yanli; Cao, Wensha; Deng, Guoxue
Abstract: Objective: The case-based learning with situated cognition theory (CBL-SCT) approach focuses on teaching over learning, making it suited to student nurse education. However, it is rare in student nurse training in pediatric surgery, and some subjective evaluations of the learning effect are still affected by the assessor. This study investigated the effect of the CBL-SCT approach on improving the nursing quality/safety and comprehensive performance of student nurses, and explored a method for analyzing the reliability of subjective evaluations. Methods: Thirty-six student nurses were divided into a control group and an experimental group and received seven days of orientation via conventional and CBL-SCT training, respectively. The learning effect was evaluated via examining their implementation of nursing quality criteria within the following month and their comprehensive clinical performance after six months. Among the evaluation indicators, professional skills, job competency, and professional quality were evaluated by assessors, whose scores were tested for consistency using Cronbach's alpha. Results: Among the 11 nursing quality criteria, the correct implementation of patient identification and communication ( t = 2.257, P = 0.031), medication-checking ( t = 5.444, P < 0.001), tumbles/bed-falling prevention ( t = 3.609, P = 0.001), pressure injury prevention ( t = 3.834, P = 0.001), catheter management ( t = 3.409, P = 0.002), and nursing record writing ( t = 2.911, P = 0.006) in the experimental group were all higher than in the control group. Six months after training, the experimental group was also higher in professional theory ( t = 4.889, P < 0.001), professional skills ( t = 2.736, P = 0.010), job competency ( t = 5.166, P < 0.001), and professional quality ( t = 16.809, P < 0.001). Cronbach's alpha test verified that the assessors' evaluations had good internal consistency and reliability for job competency (alpha = 0.847, 95% CI lower limit = 0.769), professional quality (alpha = 0.840, 95% CI lower limit = 0.759), and professional skills (alpha = 0.888, 95% CI lower limit = 0.822). Conclusions: The CBL-SCT method can help student nurses quickly change their nursing role, and Cronbach's alpha test can verify the reliability of subjective evaluations, thus indirectly reflecting the training effect equitably and objectively.